The Second and Final Presidential Debate of Donald Trump and Joe Biden: A Conceptual Metaphor Analysis - Nirwana, Ika (English Literature Study Program, 2023)
This study discusses the conceptual metaphor employed in the second and final presidential debate between Donald Trump and Joe Biden. The debate revolved around each candidate's arguments regarding the advantages and disadvantages of their presidential candidacy. The research focuses on analyzing the meaning and various types of Conceptual Metaphors, namely Ontological Metaphor, Structural Metaphor, and Orientational Metaphor. A qualitative descriptive method was utilized to analyze the data, which was collected from the YouTube Channel featuring the debates. The researcher observed and studied the videos of both Donald Trump and Joe Biden's second and final presidential debates. The data was analyzed using Lakoff and Johnson's theory (2003). The study concludes that three types of conceptual metaphors were present in the debates. A total of 16 instances of conceptual metaphors were identified, including seven ontological metaphors, two structural metaphors, and seven orientational metaphors. While the ontological metaphor was the most prevalent, its meaning was not straightforward to interpret.